Peran manajerial kepala sekolah dalam peningkatan kinerja guru: analisis model CIPP pada dua sekolah di yayasan Yohannes Gabriel Rembang - Fransiscus Soni Apri Untoro Nugroho; H. Herry Maridjo (Global Econedu, 2024)
The principal must carry out principal management in managing the school he leads. This research aims to describe the managerial role of school principals in improving teacher performance in two schools belonging to the Yohannes Gabriel Rembang Foundation. The two schools chosen were SMK Yos Sudarso Rembang and SDK St. Maria Rembang. This research uses a descriptive-evaluative method with a qualitative approach. The evaluation model used is the CIPP evaluation model (context, input, process, and product). Data collection included interviews, observation, and documentation. The research subjects were school principals and teachers. The research results show: (1) From the context evaluation, the results of supervision and educational report cards underlie the managerial role of school principals in improving teacher performance. The results of supervision and educational reports determine the principal's next managerial steps in developing a teacher performance improvement program. (2) Based on input evaluation, the role of school stakeholders (teachers, parents, alumni, the community, and good relations with the education office) supports improving teacher performance. Barriers to implementing the managerial role of school principals are time problems, employment status, finances, and infrastructure. (3) From the process evaluation, the principal's managerial functions have been carried out well, and the principal's school managerial programs for improving teacher performance are right on target. (4) From the product evaluation, the managerial role of the principal in improving teacher performance produces IHT activity products, class supervision, and teacher workshops. However, these activities still need to be expanded in scope and made sustainable.